APPLICATION OF NUMERICAL MODELING TECHNIQUES IN ELECTROMAGNETIC HYPERTHERMIA - Sathiaseelan, V. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Electromagnetic hyperthermia has been demonstrated to be a safe and useful adjuvant to ionizing radiation in the treatment of malignant tumors. However, applicators and systems for delivering the optimum treatment prescribed by the physicians are far from being available at present. Computer modeling can play a significant role in the design of better heating equipment and in improving the quality of the hyperthermia treatments currently being administered. There is an active ongoing research to develop suitable calculational models using a variety of numerical techniques. But several gaps exist in the current knowledge regarding the validity of these numerical simulations in the clinical context. The development of treatment planning systems similar to those used for radiation therapy requires resolution of these issues. Of the different numerical modeling approaches currently being developed, the finite-difference time-domain (FD-TD) technique has been extensively applied to calculate specific absorption rate (SAR) patterns in complex 3-D heterogeneous biological objects primarily because it is accurate and has a small computer burden relative to frequency-domain integral equation and finite element techniques. Following a brief review of the historical development of numerical modeling of electromagnetic interaction with biological structures in the hyperthermia context, examples of recent calculations using FD-TD technique in realistic situations in electromagnetic hyperthermia are provided. It has been observed from 2-D calculations, that the water bolus, routinely used in the clinic to provide energy coupling and surface (skin) temperature control, and the inhomogeneous tissue structures significantly modify the SAR patterns compared to patterns computed in planar and homogeneous structures. In conclusion, future areas of work are identified and discussed. [Vol. 7, No. 2, pp. 61-71 (1992), Special lssue on Bioelectromagnetic Computations]